Les Méthodes Moléculaires Pour La Caractérisation Des Champignons Phytopathogènes - Benslimane, Hamida (European Scientific Journal, ESJ, 2016)
Development of new disease-resistant varieties and the development of epidemic control strategies, require knowledge of the molecular structure and genetic relationships among the pathogen populations. Molecular methods are used to explore the diversity at the DNA level. In fact, they highlight molecular markers which are independent of the host selection, allowing study of biodiversity on the genome. These markers are most effective than a virulence markers, consequently they has become widely used in the plant pathology laboratories. This mini-review summarized the main molecular methods used; the paper describe for each one, the principle, the sequenced steps, then the advantages or inconveniences.